2022
DOI: 10.3389/fpsyg.2022.846085
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Meditation-Based Lifestyle Practices on Mindfulness, Wellbeing, and Plasma Telomerase Levels: A Case-Control Study

Abstract: Meditation involves psychophysical training which can result in a range of benefits including creating a calm mind and increasing self-awareness, relaxation, and tranquility. Increasing evidence, mostly based on short-term focused interventions, suggests that meditation-based activities may also have favorable effects on physical wellbeing including cellular aging. Hence, the aim of this study was to investigate if continued practice of meditation benefited quality of life, state of mindfulness, and plasma tel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 37 publications
0
26
0
Order By: Relevance
“…In a meta-analysis, Schutte and Malouff 104 found the effect size across all telomere studies including both novice and long-term meditators to be 0.46. Research by Dasanayaka et al 105 with long-term meditators found telomerase changes, and comparable results with meditation on telomeres length, also with strong effect sizes (0.66-0.88) for relatively small sample sizes (n < 20). 106,107 A few epigenetic studies have been conducted with meditators involving DNA methylation.…”
Section: Epigenetic and Dna Methylation Effects Of Meditationmentioning
confidence: 58%
See 1 more Smart Citation
“…In a meta-analysis, Schutte and Malouff 104 found the effect size across all telomere studies including both novice and long-term meditators to be 0.46. Research by Dasanayaka et al 105 with long-term meditators found telomerase changes, and comparable results with meditation on telomeres length, also with strong effect sizes (0.66-0.88) for relatively small sample sizes (n < 20). 106,107 A few epigenetic studies have been conducted with meditators involving DNA methylation.…”
Section: Epigenetic and Dna Methylation Effects Of Meditationmentioning
confidence: 58%
“…In Schutte et al's 104 meditation study, changes in telomere length also had a promising, moderate effect size (0.40). In a meditation review by Dasanayaka et al, 105 DNA methylation research found telomere length had a moderate effect size (0.40) for novice meditators (0.40). These findings outperformed the majority of reviewed biomedical interventions.…”
Section: Meditation Effect Sizesmentioning
confidence: 99%
“…Hence, the aim of this study was to investigate the relative telomere length, and hTERT and hTR gene expressions in long-term meditators compared to non-meditators. Using this same study cohort, we previously reported that long-term meditators had significantly higher plasma telomerase levels compared to non-meditators (22) and we also build up on our previously published data to investigate the variability of the expression of hTERT and hTR genes in relation to plasma telomerase levels.…”
Section: Introductionmentioning
confidence: 86%
“…Table 1 summarizes the baseline characteristics of the study population which have been described before (22). Briefly, nineteen individuals in each group of 30 participants (63.34%) were male with an average age of 43 years.…”
Section: Characteristics Of Study Populationmentioning
confidence: 99%
See 1 more Smart Citation